The larva of Parasetodes respersellus (Rambur 1841) with notes on its habitat and European distribution (Trichoptera: Leptoceridae) - Móra, Arnold; Juhász, Péter; Kiss, Béla; Müller, Zoltán; Málnás, Kristóf (Zootaxa, 2014)
Two larvae collected from the River Tisza were recognized to belong to the genus Parasetodes according to the available generic description. The fact that Parasetodes respersellus is the only European/Western Palaearctic representative of the genus enabled us to describe the hitherto unknown larva of this species based on the collected specimens. Diagnostic features to distinguish the genus from other Central European genera are discussed. Possible species-specific characters are compared with those of other previously described species of the genus. Some notes on larval habitat and the European distribution of P. respersellus are given.